PATIENTS' HEALTH HISTORY AND LIFE EXPERIENCES REGARDING HYPERTENSION CONTROL: THE MODERATING ROLE OF SELF-CARE AGENCY - Fitriah Fitriah; Mustofa Haris; Rodiyatun Rodiyatun; Zakkiyatus Zainiyah (Universitas Airlangga, 2026)
Hypertension is a major cause of cardiovascular disease and premature death worldwide. This study aimed to analyze the influence of patient health history and life experiences on hypertension control moderated by self-care agency in fulfilling Activities of Daily Living (ADL). The study design was a cross-sectional observational analytical study. The independent variables were health history, life experiences, and the dependent variable was hypertension control. The sample was hypertension patients at the Heart Disease Clinic and Internal Medicine Clinic of Anna Medika Madura Hospital and Syamrabu Bangkalan Hospital. 200 patients were selected using purposive sampling for 2 months. Self-care agency data were collected using the Self-Care Agency Questionnaire (SCAQ), health history questionnaires, life experiences based on the development of WHO step instruments, and short-form health surveys. Hypertension control variables were measured using a manual sphygmomanometer and questionnaires. Data analysis used descriptive statistics and logistic regression. The results of the logistic regression statistical test showed an interaction between current medical history and self-care agency with p values = 0.004, OR: 3.439 CI: (1.44-8.26) and an interaction between life experience and self-care agency with p values = 0.012 <0.05, OR: 2.674, CI: (1.22-5.90), so the influence of health history on hypertension control becomes stronger if self-care agency is high. Likewise, self-care agency strengthens the relationship between life experience and hypertension control. Increasing self-care agency can strengthen the positive impact of health history and life experience on hypertension control.